A Highly Efficient Glycosidation of Glycosyl Chlorides by Using Cooperative Silver(I) Oxide–Triflic Acid Catalysis. Issue 36 (2nd June 2020) - Geringer, Scott A.; Singh, Yashapal; Hoard, Daniel J.; Demchenko, Alexei V.
Abstract: Following our discovery that silver(I) oxide‐promoted glycosylation with glycosyl bromides can be greatly accelerated in the presence of catalytic TMSOTf or TfOH, we report herein a new discovery that glycosyl chlorides are even more effective glycosyl donors under these reaction conditions. The developed reaction conditions work well with a variety of glycosyl chlorides. Both benzoylated and benzylated chlorides have been successfully glycosidated, and these reaction conditions proved to be effective in coupling substrates containing nitrogen and sulfur atoms. Another convenient feature of this glycosylation is that the progress of the reaction can be monitored visually; its completion can be judged by the disappearance of the characteristic dark color of Ag2 O. Abstract : Glycosyl donor activation : Efficient glycosylations of both benzoylated and benzylated glucosyl, galactosyl, and mannosyl chlorides have been accomplished through a strategy based on activation using 0.50 equiv of silver(I) oxide and 0.25–0.50 equiv of triflic acid.